(untitled) (Journal of the College of Basic Education, 2025)
The aim of the present research is to examine mood moderation among students of the Kindergarten Department. To achieve the research objectives, the researcher adopted a descriptive approach. The research community consisted of students from the Kindergarten Department at Al-Mustansiriyah University, College of Basic Education, across all four morning study levels (first, second, third, and fourth years). A sample of 300 students was selected from these levels using a proportional stratified random sampling method. To measure mood moderation, the researcher adopted the scale developed by (Naama, 2020), based on Martin Seligman’s theory. The scale consists of 27 items, and the statistical properties of the items were verified using discriminative power and the relationship of each item with the total score of the scale, as well as the relationship of the item score with the total score of each domain. The psychometric properties of the scale, including validity and reliability, were also confirmed. The reliability coefficient, using the test-retest method, was found to be 0.85, while the Cronbach’s alpha coefficient was 0.80. For statistical data analysis, the researcher used Pearson correlation coefficient, one-sample t-test, independent samples t-test, Chi-square test, and Cronbach’s alpha equation. The results revealed that the sample of the study exhibited a high level of mood moderation.